Environmental Problems and the Question of Intergenerational Justice from the Kantian Perspective - Timothy Adie OKPE; Samuel Akpan BASSEY (Budapest International Research and Critics University, 2018)
In this paper, I aim at unraveling some of the numerous environmental practices in Nigeria that often times leads to environmental degradation which to a larger extent affects us presently and the effect on the future generation is better imagined if positive actions are not taken to check this trend. It is on the basis of this using one of Kant's categorical imperative that states that